Nanoencapsulated quercetin for the treatment of liver cancer: a literature review - Pedrolo, Bruna Garcia; Moraes, Jefferson Potiguara de; Simão, Éder Maiquel; Rech, Virginia Cielo; Ourique, Aline Ferreira; Sagrillo, Michele Rorato; Silva, Ivana Zanella da (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
Quercetin, a natural flavonoid found in many kinds of food such as fruit and vegetables, is one of the most prominent dietary antioxidants known for its anticarcinogenic potential. In the last decade, there has been an increase in studies involving this flavonoid. The aim of this review is to evaluate the association between nanoparticles with quercetin and hepatocarcinoma or liver cancer. A review of papers published in the last 10 years in PubMed, Web of Science and Scopus databases was performed using quercetin and nanoparticles as descriptors. Papers containing the descriptors quercetin, nanoparticles, liver cancer (hepatocarcinoma) were classified. The increase in studies related to nanoencapsulated quercetin indicates its therapeutic potential, which could be powerful in cancer prevention. In vivo and in vitro studies suggest that quercetin has anticancer effects that inhibit tumor growth, discontinuing cell cycle and inducing apoptosis. The need for further studies about the potential therapeutic effects of quercetin nanoparticles is highlighted.